Food safety in China from North American and European perspectives. Issue 2 (3rd July 2019) - Lee, Harry F.; Boccalatte, Margherita
ABSTRACT: Food safety crises have constituted a persistent challenge for the Chinese government and people. Because of international trade, consumers' concern regarding the safety of food products imported from China is increasing in many countries. Yet, no systematic investigation has examined the perception of Western respondents regarding the safety of food imports coming from China. This study, based on an online survey ( n  = 289) between April and May 2017, is an initial attempt to investigate the perception of consumers in Europe and North America regarding different food safety issues and regulations in the People's Republic of China and their attitudes towards food products imported from China. Our results show that socioeconomic and demographic characteristics and the influence of different types of media were not related to the perceptions and attitudes towards food safety. But, we found a strong relationship between the perception of the food safety regulations in China and the personal consumption of food products imported from China. In addition, a positive relationship was discovered between having been to China and the purchase of food products imported from China. Our findings suggest that investments in the promotion of the knowledge of food safety regulations implementation in China would lead to an increase in the export of food products. Also, the positive relationship between having been to China and the purchase of food products imported from China should be further investigated to consider the implications for tourism and food trade in China.